Brincidofovir for the treatment of human adenovirus infection in pediatric solid organ transplant recipients: A case series. (18th June 2020) - Londeree, Jackson; Winterberg, Pamela D.; Garro, Rouba; George, Roshan P.; Shin, Stella; Liverman, Rochelle; Serluco, Anastacia; Romero, Rene; Yildirim, Inci
Abstract: HAdV viremia can cause significant morbidity among pediatric recipients of SOT with variability in incidence and severity of disease based on the type of allograft. Currently, there are no US FDA–approved treatments for HAdV infections, and historically, the mainstay of treatment has been decreasing immunosuppression, with antiviral therapies reserved for those with severe disease. We describe the treatment of four pediatric SOT recipients (two kidney, one combined kidney‐liver, and one liver) presenting with HAdV disease at our institution using brincidofovir. Our case series highlights the variability in presentation and the potential for severe disease in pediatric SOT recipients as we review disease presentation, disease course, complications, and treatment with brincidofovir.